Application and Numerical Simulation of a Portable Falling Weight Deflectometer for Compaction Quality Evaluation of Levee Embankment Filling Based on Abaqus - Ma, Xiaoze; Ai, Chenghao; Gu, Menghui; Zhang, Shuoxin; Zhou, Yang; Wang, Liangxiang (Journal of Research in Science and Engineering, 2026)
To achieve rapid, non-destructive, and quantitative evaluation of compaction quality in levee embankment construction, this study takes the Wenchao Flood Diversion River embankment project as a case study and integrates field testing using a portable falling weight deflectometer (PFWD) with finite element numerical simulation based on Abaqus. The mechanical response and compaction quality of embankment filling materials under different layer thicknesses were systematically investigated. Material parameters of the dam fill were obtained from PFWD field tests and converted into equivalent Young’s modulus values. A finite element model was established in Abaqus to simulate the transient impact loading process, and the rationality of the modeling approach and parameter inversion method was verified through comparison between numerical results and field measurements. The results indicate that layer thickness has a significant influence on the elastic deformation and resilient modulus of the embankment body, with thinner layers being more favorable for improving the overall stiffness of the structure. The relative error between simulated and measured central deflection values was less than 5%, demonstrating good agreement. The proposed approach provides a reliable basis for compaction quality evaluation and optimization of construction parameters in levee embankment filling projects by combining non-destructive field testing with numerical simulation.